1999
DOI: 10.1002/(sici)1520-6807(199907)36:4<347::aid-pits7>3.3.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

How teachers respond to concerns about misbehavior in their classroom

Abstract: The present study examined kindergarten to Year Two teachers' responses to concern about classroom misbehavior in terms of (a) support they access, (b) strategies they use, and (c) information they require to more effectively deal with misbehavior. The extent to which teachers' confidence in behavior management mediated the relationship between students' misbehavior and a, b, and c was also examined. Results indicated that concern about their students' misbehavior was negatively associated with teachers' confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 0 publications
2
48
0
1
Order By: Relevance
“…These results extend the findings of previous studies which reported that teachers tend to use positive ways of dealing with children's behavior problems, but they do deliver punishment as well (Docking, 1980;Papatheodorou, 2000) Many explanations could be given for the results. Teachers do not have enough information and understanding about how management practices should be used (Martin, Linfoot, & Stephenson, 1999). It is notable that some teachers are inadequately trained to deal with students with behavior problems and may actually exacerbate the misbehavior (Pettit, Bates, & Dodge, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…These results extend the findings of previous studies which reported that teachers tend to use positive ways of dealing with children's behavior problems, but they do deliver punishment as well (Docking, 1980;Papatheodorou, 2000) Many explanations could be given for the results. Teachers do not have enough information and understanding about how management practices should be used (Martin, Linfoot, & Stephenson, 1999). It is notable that some teachers are inadequately trained to deal with students with behavior problems and may actually exacerbate the misbehavior (Pettit, Bates, & Dodge, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…As teachers develop experientially they are then in a position to reflect on their practices and seek a boarder base for their theoretical framework. Martin et al (1999) studied the relationships between teacher confidence and responses to misbehaviour in schools. They found that teachers frequently requested information about behaviours and positive strategies and that this suggested that current teacher education did not provide pre-service teachers with the skills to successfully manage problem behaviours.…”
Section: Class Management Skillsmentioning
confidence: 99%
“…A number of studies (Arbuckle & Little, 2004;Martin, et al, 1999;Stephenson, Linfoot, & Martin, 2000) discuss the concern of teachers with the level of distractibility of students and lack of time on task. In contrast parents often report that while their children lack concentration in school they can spend hours in full concentration on their hobbies especially on computer games.…”
Section: Engagement Of Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…Student problem behavior is a fundamental concern for teachers, yet many do not feel equipped to prevent or address the behavior (Allday et al, 2011). Teachers have consistently reported feeling under-educated and unprepared to manage challenging behaviors (Clunies-Ross, 2008;Martin, Linfoot, & Stephenson, 1999). For example, when Baker (2005) surveyed teachers, nearly half of their sample felt ill-equipped to manage student behavior.…”
Section: Implementation Barriersmentioning
confidence: 99%